2008
DOI: 10.1029/2008gc001965
|View full text |Cite
|
Sign up to set email alerts
|

Magmatic and tectonic extension at mid‐ocean ridges: 1. Controls on fault characteristics

Abstract: [1] We use 2-D numerical models to explore the thermal and mechanical effects of magma intrusion on fault initiation and growth at slow and intermediate spreading ridges. Magma intrusion is simulated by widening a vertical column of model elements located within the lithosphere at a rate equal to a fraction, M, of the total spreading rate (i.e., M = 1 for fully magmatic spreading). Heat is added in proportion to the rate of intrusion to simulate the thermal effects of magma crystallization and the injection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
233
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(254 citation statements)
references
References 121 publications
(172 reference statements)
21
233
0
Order By: Relevance
“…However, the additional influence of fault rotation will allow sustained slip on normal faults formed in thicker lithosphere than would be permitted if fault dip remained fixed at high angle. This is consistent with previous numerical simulations of fault development at mid-ocean ridges by Behn and Ito [2008], who found that a force balance model could only predict fault life span in an elasto-plastic lithosphere if it incorporated the reduction in fault dip observed in their numerical simulations. This suggests that both the finite yield strength of the lithosphere and the flexural rotation mechanism presented here are important components to the physics of normal fault growth.…”
Section: Rheologic Controls On Rotation Rate and Life Span Of Normalfsupporting
confidence: 80%
See 2 more Smart Citations
“…However, the additional influence of fault rotation will allow sustained slip on normal faults formed in thicker lithosphere than would be permitted if fault dip remained fixed at high angle. This is consistent with previous numerical simulations of fault development at mid-ocean ridges by Behn and Ito [2008], who found that a force balance model could only predict fault life span in an elasto-plastic lithosphere if it incorporated the reduction in fault dip observed in their numerical simulations. This suggests that both the finite yield strength of the lithosphere and the flexural rotation mechanism presented here are important components to the physics of normal fault growth.…”
Section: Rheologic Controls On Rotation Rate and Life Span Of Normalfsupporting
confidence: 80%
“…Second, numerous studies, including Chapters 2 and 3 of this thesis have shown that normal fault evolution is controlled by the build-up of elasto-plastic stresses in the faulted layer. This build-up is generally attributed to the flexural readjustment of the footwall and hanging wall blocks in response to fault growth [Buck, 1988;Weissel and Karner, 1989;King et al, 1988], and has consequences for both fault rotation [Olive and Behn, 2014;Olive et al, 2014b] and fault life span, hereafter defined as the amount of horizontal offset that can be accommodated on a fault before it is abandoned in favor of a new fault [Forsyth, 1992;Buck, 1993;Lavier et al, 2000;Behn and Ito, 2008]. It is therefore unclear to what extent a visco-plastic description of the lithosphere can produce behaviors that are relevant for understanding geological systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is conceivable that the faults observed in the PDR passively rotated into their current orientation. Barring passive rotation, however, they were likely not part of the fault system inferred from seafloor scarps [Bohnenstiehl and Carbotte, 2001] and modeled as a response to flexural forces during seafloor spreading [Buck et al, 2005;Behn and Ito, 2008;Ito and Behn, 2008]. Instead, the faults were part of a set that is driven primarily by magmatic accretionary processes [Karson et al, 2002a;Carbotte et al, 2003] and, as suggested here, varying pressure conditions due to the influence of hydrothermal fluid flow on fault mechanics.…”
Section: An Evaluation Of Axial Versus Axial Flank and Off-axis Faultmentioning
confidence: 99%
“…In contrast, recent numerical models have implicitly questioned the importance of subaxial faults in fast spreading centers. Mechanical models suggest that faulting is less important than dike injection along fast spreading centers [Buck et al, 2005;Behn and Ito, 2008;Ito and Behn, 2008]. Additionally, recent transport models suggest that hydrothermal systems can develop without the planar, anisotropic permeability, and mineral sealing associated with faults [Fontaine and Wilcock, 2007;Coumou et al, 2008].…”
Section: Introductionmentioning
confidence: 99%